″Peculiarities of the organization of professional foreign language training of future software engineers on the basis of an integrative approach″ - Mykytyshyn, A. A. (Problems of Engineer-Pedagogical Education, 2018)
The article discusses peculiarities of organizing the process of training future software engineers for professional communication in a foreign language. The paper discusses the didactic potential of information and web technologies and provides the description of the distance course «Basics of professional foreign language communication», which serves as a background for the implementation of the experimental methodology for professional foreign language training of future software engineers on the basis of an integrative approach. The research is grounded on the analysis of theoretical and practical bases of the organization of professional foreign language training of future software engineers in higher education institutions. It applied such scientific methods as literature review, synthesis, generalization, evaluation of students‟ learning results, testing and survey. The outcome is the distance learning course «Basics of professional foreign language communication», developed for the students of technical majors with the purpose of enhancing their readiness to conduct professional foreign language communication. The suggested methodology applies the basics of the integrative approach, which contributes to thorough and comprehensive acquisition of the corresponding competence.